PENGARUH PENGATURAN KERJA FLEKSIBEL, KECERDASAN EMOSIONAL, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI JAKARTA - Qonita, Siti Nur; Soemartono, Triyuni; Marwan, Jubery (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to obtain empirical evidence on the influence of flexible work arrangements, emotional intelligence, and work competence on employee performance at the Tourism and Creative Economy Office of DKI Jakarta Province. Changes in work patterns and increasing performance demands in the public sector require organizations to manage human resources in a more adaptive and professional manner. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 75 employees as research respondents. The research instruments were developed using a Likert scale to measure each research variable. The collected data were analyzed using statistical techniques to examine the relationships and effects among variables. The results indicate that flexible work arrangements have a positive and significant effect on employee performance, suggesting that work flexibility enhances employee effectiveness and productivity. Furthermore, emotional intelligence and work competence were also found to have positive and significant influences on employee performance. These findings emphasize that the implementation of flexible work systems, supported by strong emotional intelligence and adequate work competence, plays a crucial role in improving employee performance in the public sector, particularly within the Tourism and Creative Economy Office of DKI Jakarta Province.